(untitled) (Research, Society and Development, 2021)
This article addresses the (im) possibility of acknowledging dual socio-affective paternity and maternity, in cases where the third party, a genetic material donor, is willing to waive his right. The question raised is whether the Brazilian courts, when deciding only for the recognition of the socio-affective family, consisting of two fathers or two mothers, in cases of pregnancies with multiple parental ties due to the donation of genetic material by a third party, take into account the principle in the best interest of the child or adolescent. Therefore, it is necessary, therefore, to make an analysis of the positions established by the Brazilian courts. The scientific article was developed from the qualitative method, through a doctrinal and jurisprudential review, as well as a bibliographic survey in journals and scientific articles. The research method was hypothetical-deductive. The research presents a brief study on the institute of family law, which is later dealt with social paternity and maternity, ending with the analysis of the position adopted by Brazilian courts with regard to cases of pregnancies with multiple ties. As a result of this work, it was possible to verify that the position that begins to spread by the Brazilian courts, in cases of donation of genetic material by a third party and who has no interest in participating in the child’s life, is in a favorable sense, that is, the possibility of there is only recognition of dual socio-affective paternity and maternity in favor of the child’s best interests.